2018
DOI: 10.1016/j.fuel.2017.11.115
|View full text |Cite
|
Sign up to set email alerts
|

Performance and degradation mechanisms of CLC particles produced by industrial methods

Abstract: A promising copper based oxygen carrier produced using industriallyrelevant manufacturing equipment has been aged in IFPEN's 10 kW th Chemical Looping Combustion pilot plant. Methane combustion was performed at 900°C for 160h with an OC/fuel ratio of 1.2. While full methane conversion to CO 2 and water was achieved in the early stage of the experiment, fast deactivation was observed. The oxygen carrying particles were thoroughly characterized at various stages of the ageing experiment, from which a pathway lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…These units can be classified depending on the fluid dynamic characteristics of the fuel reactor. Thus, 10 kW th CLC units located at ICB-CSIC [10,11] and IFP [12] were designed for bubbling fluidized bed conditions in the fuel reactor, while the fuel reactor in the 120 kW th unit and TUV [13][14][15] and 150 kW th unit at SINTEF [16] were circulating fluidized beds. Recently, the 120 kW th CLC unit at TUV has been modified to include a wider section in the bottom part of the reactor, but maintaining the circulation of solids in a narrow riser above the bottom bed [17].…”
Section: Introductionmentioning
confidence: 99%
“…These units can be classified depending on the fluid dynamic characteristics of the fuel reactor. Thus, 10 kW th CLC units located at ICB-CSIC [10,11] and IFP [12] were designed for bubbling fluidized bed conditions in the fuel reactor, while the fuel reactor in the 120 kW th unit and TUV [13][14][15] and 150 kW th unit at SINTEF [16] were circulating fluidized beds. Recently, the 120 kW th CLC unit at TUV has been modified to include a wider section in the bottom part of the reactor, but maintaining the circulation of solids in a narrow riser above the bottom bed [17].…”
Section: Introductionmentioning
confidence: 99%
“…It should be said that copper oxide impregnated on materials based on γ-Al2O3 has shown low attrition, [89]. Unfortunately, the copper oxide reacts with the support to CuAl2O4, which is still a good oxygen carrier but without the excellent CLOU properties of CuO, [90][91][92]. But so far only a limited number of copper oxides have been examined, and the unique performance of copper-CLOU materials makes it worthwhile to pursue the investigation of copper-based materials.…”
Section: 3 Cu-based Materialsmentioning
confidence: 99%
“…[11,12] While the copper-rich fines formed by attrition are related to the outward migration of the copper, the increased porosity in the particles is associated to the alumina phase transition. [7,13] Recently, Cabello et al reported that the mechanical integrity of the OC is not affected when the redox cycling is carried out at 800 °C, compared to 900 °C or above. [14] This difference in the material behaviour could arise from multiple phase transformations during reactions, owing to high chemical and thermal stress during the redox cycles.…”
Section: Introductionmentioning
confidence: 99%